The Impact of Mind Mapping on Junior High School Students’ Short Story Writing Proficiency - Muhammad Arbain; Irfan Perdana; Nur Hasby (Lembaga Pengembangan Kinerja Dosen, 2024)
This research focuses on assessing the influence of mind mapping as a learning strategy on the short-story writing proficiency of junior high school students studying English. In particular, this research examines the extent to which mind mapping affects different components of writing proficiency, such as organization, coherence, and creativity. The study adopted a quasi-experimental pretest–posttest control group design, utilizing a purposive sample of 50 students in the eighth grade. The experimental group was instructed through the use of mind mapping techniques, whereas the control group received instruction via conventional teaching methods. Data were collected through pretest and posttest written tasks and analyzed using SPSS to perform both descriptive and inferential statistical procedures. Results obtained from the independent-samples t-test revealed a significant improvement in the experimental group’s writing performance, with a p-value of 0.029. These results indicate that mind mapping is an effective strategy for improving short-story writing skills among junior high school EFL learners, suggesting its potential for enhancing students' writing abilities in a more engaging and organized way.